PENEGAKAN HUKUM TERHADAP JUDI ONLINE DI INDONESIA: TANTANGAN DALAM MEMBERANTAS KEJAHATAN SIBER TRANSNASIONAL - Dina Octavia; Ghita Audi (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of information technology and the internet has brought significant changes to society, including the emergence of various forms of cybercrime, one of which is online gambling. Online gambling is a form of digital-based gambling that is easily accessible to various groups and has negative impacts on social, economic, psychological aspects, and family stability. This study aims to analyze law enforcement against online gambling practices in Indonesia, identify the challenges in combating it as a transnational cybercrime, and formulate strategies to improve the effectiveness of law enforcement. The research method used is normative legal research with a literature review approach, employing statutory, conceptual, and comparative approaches. The data sources include primary, secondary, and tertiary legal materials analyzed using descriptive-qualitative methods. The results indicate that law enforcement against online gambling in Indonesia has been carried out through various legal instruments, such as the Criminal Code, the Electronic Information and Transactions Law, and anti-money laundering regulations, involving the police, the Ministry of Communication and Digital Affairs, and the Financial Transaction Reports and Analysis Center. However, law enforcement still faces various challenges, including limitations in cross-border jurisdiction, difficulties in digital evidence collection, the use of anonymity technologies, institutional capacity constraints, and obstacles in international cooperation. Therefore, strengthening regulations, enhancing law enforcement capacity, expanding cross-border cooperation, and increasing public education are necessary strategies to improve the effectiveness of combating online gambling in Indonesia.